Memory Inflation Drives Tissue-Resident Memory CD8+ T Cell Maintenance in the Lung After Intranasal Vaccination With Murine Cytomegalovirus - Morabito, Kaitlyn M.; Ruckwardt, Tracy J.; Bar-Haim, Erez; Nair, Deepika; Moin, Syed M.; Redwood, Alec J.; Price, David A.; Graham, Barney S. (Frontiers in Immunology, 2018)
Tissue-resident memory T (TRM) cells provide first-line defense against invading pathogens encountered at barrier sites. In the lungs, TRM cells protect against respiratory infections, but wane more quickly than TRM cells in other tissues. This lack of a sustained TRM population in the lung parenchyma explains, at least in part, why infections with some pathogens, such as influenza virus and respiratory syncytial virus (RSV), recur throughout life. Intranasal vaccination with a murine cytomegalovirus (MCMV) vector expressing the M protein of RSV (MCMV-M) has been shown to elicit robust populations of CD8+ TRM cells that accumulate over time and mediate early viral clearance. To extend this finding, we compared the inflationary CD8+ T cell population elicited by MCMV-M vaccination with a conventional CD8+ T cell population elicited by an MCMV vector expressing the M2 protein of RSV (MCMV-M2). Vaccination with MCMV-M2 induced a population of M2-specific CD8+ TRM cells that waned rapidly, akin to the M2-specific CD8+ TRM cell population elicited by infection with RSV. In contrast to the natural immundominance profile, however, coadminstration of MCMV-M and MCMV-M2 did not suppress the M-specific CD8+ T cell response, suggesting that progressive expansion was driven by continuous antigen presentation, irrespective of the competitive or regulatory effects of M2-specific CD8+ T cells. Moreover, effective viral clearance mediated by M-specific CD8+ TRM cells was not affected by the coinduction of M2-specific CD8+ T cells. These data show that memory inflation is required for the maintenance of CD8+ TRM cells in the lungs after intranasal vaccination with MCMV.